Montagem e operação de um secador pneumático tipo flash - Freire, Luziany Adyja da Costa (2011)
In this work, a pneumatic dryer has been designed and assembled in laboratory scale in order to study and evaluate configurations more efficient for application in drying of important materials of Northeast region in Brazil. The equipment was tested with drying of corn and rice grains, in conditions of temperature and air velocity at 80 oC and 35 m/s, respectively. For this type of dryer, it is recommended to work at temperatures above 200 °C and air velocity with higher dynamic pressure. However, even under operating conditions below what it is recommended, the results obtained with the pneumatic dryer were satisfactory. In addition, experiments of drying were performed by using a cabinet dryer (batch dryer) under the same conditions used in the pneumatic dryer. Flash one curves for the corn were fitted satisfactorily by applying of the Lewis model, while a better agreement was found for rice by using the Page model. The data obtained with both drying processes allowed to compare the performance between pneumatic and batch dryers. In respect to drying rate, the pneumatic dryer presented a similar performance to the batch dryer during processing with corn and a superior performance to the last one during processing with rice. Therefore, it was possible to verify that the pneumatic dryer assembled in this preliminar study can be applied for different materials and under different operating conditions